2020
DOI: 10.3390/foods9101488
|View full text |Cite
|
Sign up to set email alerts
|

The Freeze-Drying of Foods—The Characteristic of the Process Course and the Effect of Its Parameters on the Physical Properties of Food Materials

Abstract: Freeze-drying, also known as lyophilization, is a process in which water in the form of ice under low pressure is removed from a material by sublimation. This process has found many applications for the production of high quality food and pharmaceuticals. The main steps of the freeze-drying process, such as the freezing of the product and primary and secondary drying, are described in this paper. The problems and mechanisms of each step of the freeze-drying process are also analyzed. The methods necessary for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(114 citation statements)
references
References 130 publications
3
85
0
4
Order By: Relevance
“…The structure of microparticles was similar to a broken glass pieces of various sizes, which was also found in previous studies ( 48 ). At low temperatures of freeze-drying the physical state is important for frozen food stability ( 49 ). A glassy structure with irregular shape might protect the bioactive compounds against heat and oxygen exposure ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…The structure of microparticles was similar to a broken glass pieces of various sizes, which was also found in previous studies ( 48 ). At low temperatures of freeze-drying the physical state is important for frozen food stability ( 49 ). A glassy structure with irregular shape might protect the bioactive compounds against heat and oxygen exposure ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…The process takes place at a low temperature, where biologically active compounds remain preserved in large quantities. Over the last decade, freeze-dried food has gained popularity, especially for fruits such as berries [49]. Hammami and Rene [50] reported that optimal freeze-drying parameters for strawberry are 30 Pa and 50 • C of a drying plate, and that under these conditions, neither off-flavors nor the off-tastes were formed.…”
Section: Freeze-dryingmentioning
confidence: 99%
“…The end of this process is the equivalent of reaching a positive temperature in the food. Freeze-drying consists of three stages: freezing, sublimation, and desorption [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The porous structure created during the freeze-drying process is useful in the production of food powders because of its good rehydration ability. Nevertheless, with this porous structure, active compounds can be affected by oxygen or water from the environment, while the porosity increases the contact area [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%